The Determinants of Intention to Adopt Islamic Financial Technology in Indonesia - Pardiansyah, Elif; Sobari, Nurdin; Usman, Hardius (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2022)
This study analyses the factors determining the intention to adopt Islamic financial technology for Muslim users in Indonesia. This study uses a quantitative approach to analyze the determinant of intention to adopt Islamic fintech. The analysis was carried out using Structural Equation Modeling (SEM) with the SmartPLS application tool to examine the relationship between variables in the model. 205 respondents were selected through a purposive sampling technique to get Muslim respondents in Jabodetabek and Bandung who had used fintech applications but had not used sharia fintech. The results showed that the determinant of intention to use Islamic fintech is positively and significantly influenced by Perceived Usefulness (PU) and attitude (A). Meanwhile, perceived ease of use (PEOU), trust (T), and religiosity (R) have a positive but not significant effect on the intention to use (ITU) Islamic fintech. Indirectly, perceived ease of use and trust has a positive and significant effect on the intention to use Islamic fintech through perceived usefulness (PU) and attitude variables; perceived usefulness (PU) and religiosity (R) have a positive and significant effect on the intention to use Islamic fintech through attitude.